Díaz-Guardamino, M.; García Sanjuán, L.; Wheatley, D. (2015): The Prehistoric Lives of Prehistoric Monuments in Iron Age, Roman and Medieval Europe - Aranda Jiménez, Gonzalo (SPAL - Revista de Prehistoria y Arqueología, 2017)
Díaz-Guardamino, M.; García Sanjuán, L.; Wheatley, D. (2015): The Prehistoric Lives of Prehistoric Monuments in Iron Age, Roman and Medieval Europe. Oxford, Oxford University Press, 356 pp. ISBN: 978-0-19-872460-5